2015
DOI: 10.3945/ajcn.113.069807
|View full text |Cite
|
Sign up to set email alerts
|

Malian children with moderate acute malnutrition who are treated with lipid-based dietary supplements have greater weight gains and recovery rates than those treated with locally produced cereal-legume products: a community-based, cluster-randomized trial

Abstract: RUSF was more effective, but more costly, than other dietary supplements for the treatment of MAM; CSB++ yielded intermediate results. The benefits of treatment should be considered in relation to product costs and availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 28 publications
8
80
0
1
Order By: Relevance
“…For example, no differences in growth were found in 6- to 12-month-old infants consuming soya, casein or rice formula along with complementary feeding ( 40 ) . In infant studies, plant protein sources have been as efficacious as other ready-to-use foods for growth ( 41 , 42 ) , despite possibly poor protein quality identified in our study. Dietary variety beyond food aid may contribute to these findings as well.…”
Section: Discussionmentioning
confidence: 69%
“…For example, no differences in growth were found in 6- to 12-month-old infants consuming soya, casein or rice formula along with complementary feeding ( 40 ) . In infant studies, plant protein sources have been as efficacious as other ready-to-use foods for growth ( 41 , 42 ) , despite possibly poor protein quality identified in our study. Dietary variety beyond food aid may contribute to these findings as well.…”
Section: Discussionmentioning
confidence: 69%
“…Few studies have reported on morbidity in children with moderate wasting or moderate acute malnutrition (MAM) [9][10][11][12][13][14][15] and most based only on symptom-recall. Current case definitions of MAM includes children with moderate wasting and/or a mid-upper arm circumference (MUAC) between 115 and 125 mm [16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the efficacy of milk-based products, certain milk-free formulations have been shown to be equivalent in the management of MAM (183,(192)(193)(194) , whereas in other studies, these formulations were less effective regarding the treatment of MAM (155,(195)(196)(197)(198)(199)(200) as well as SAM (201) . While a reduced efficacy of preparations without milk was generally most pronounced in children below the age of 2 years, it has been suggested that milk-free products should be used preferentially in the treatment of undernourished children older than 2 years, whereas the younger age group may depend more on products containing dairy products, especially if breast-feeding has been terminated (201,202) .…”
Section: Strategies To Reduce the Costs Of Milk-based Ready-to-use Foodsmentioning
confidence: 99%